An NTS-CeA projection modulates depression-like behaviors in a mouse model of chronic pain - Shilang He; Xuelin Huang; Jun Zheng; Yuehong Zhang; Xiangcai Ruan (Neurobiology of Disease, 2022)
Depressive symptoms comorbid with chronic pain are a common health problem, but the underlying neural circuit mechanisms remain elusive. Here, we identify a glutamatergic projection from the nucleus of the solitary tract (NTS) to the central nucleus of the amygdala (CeA) that mediates depression-like behaviors in a chemotherapy-induced neuropathic pain model. Inhibition or ablation of the glutamatergic NTS neurons alleviates depressive but not hypersensitive behaviors in these mice. The projected neurons form excitatory synapses with somatostatin-expressing neurons in the CeA. Silencing the NTS-CeA projection alleviates depressive but not hypersensitive behaviors, whereas activating the proection promotes depressive behaviors. In addition, in naïve mice, activation of the NTS-CeA projection induces obvious depressive behaviors that can be blocked by silencing the CeA somatostatin-expressing neurons. Together, we reveal a modulatory role of the NTS and its glutamatergic projection to the CeA circuit in modulating depression-like behaviors comorbid to chronic pain.